2011
DOI: 10.1111/j.1872-034x.2011.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired activities of cyclic adenosine monophosphate‐responsive element binding protein, protein kinase A and calcium‐independent phospholipase A2 are involved in deteriorated regeneration of cirrhotic liver after partial hepatectomy in rats

Abstract: CREB dysfunction, mediated by PKA and iPLA2 suppression, may be involved in the deteriorated liver regeneration in the cirrhotic rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These data imply that iPLA 2 β protein may be subjected to degradation at post translational levels during NASH. It is shown that iPLA 2 expression is decreased in rat cirrhotic livers [ 116 ], and may support iPLA 2 β as a target for degradation during severe liver injury. Currently, no published data on iPLA 2 β or PLA2G6 expression in livers of NAFLD/NASH patients are available.…”
Section: Ipla 2 β and De Novo Lipogenesis Genementioning
confidence: 99%
“…These data imply that iPLA 2 β protein may be subjected to degradation at post translational levels during NASH. It is shown that iPLA 2 expression is decreased in rat cirrhotic livers [ 116 ], and may support iPLA 2 β as a target for degradation during severe liver injury. Currently, no published data on iPLA 2 β or PLA2G6 expression in livers of NAFLD/NASH patients are available.…”
Section: Ipla 2 β and De Novo Lipogenesis Genementioning
confidence: 99%